Burnout syndrome and the protective role of resilience among university professors: a cross-sectional study of associated psychosocial and physical factors - Maria Jose Alban Guijarro; Luis Chauca-Bajaña; Carlos Martínez Florencia; José Dionel Alban Sanchez; Miguel Álvarez Aviles; Denisse Arroyo-Apolo; Andrea Ordoñez Balladares; Manuel Roberto Tolozano-Benites; Alba Perez-Jardon; Byron Velásquez Ron (Frontiers in Psychology, 2025)
BackgroundBurnout syndrome is increasingly common among university professors, who face demanding workloads, academic pressures, and challenging work environments. This condition negatively impacts not only their emotional and physical well-being but also the quality of education. This study aimed to determine the prevalence of burnout syndrome and its associations with physical symptoms, resilience, and sociodemographic variables among professors at the University of Guayaquil.MethodsA cross-sectional study was conducted with a random sample of 334 university professors. Three instruments were used: the Maslach Burnout Inventory (MBI), a physical symptomatology questionnaire, and the Connor-Davidson Resilience Scale. Data analysis was performed using SPSS version 27. Chi-square tests were applied to identify associations between variables, and simple linear regression analysis was used to explore predictors of burnout, particularly the role of resilience and physical symptoms.ResultsOf the professors surveyed, 52.4% were men and 47.6% women. Emotional exhaustion had a mean of 22.05 (SD = 5.665), and depersonalization had a mean of 8.37 (SD = 3.092). Physical symptoms were reported by 71.6% of participants, with nausea (86.2%) and respiratory issues (81.1%) being the most prevalent. Regression analysis revealed that employment status and several physical symptoms (e.g., sleep disturbances, muscle tension, gastrointestinal discomfort) were significantly associated with higher burnout levels (p < 0.05). Resilience was inversely associated with burnout, confirming its protective role (p < 0.01).ConclusionA significant proportion of university professors experience moderate to high levels of burnout, especially emotional exhaustion and depersonalization. Resilience was identified as a key protective factor, emphasizing the importance of institutional strategies that promote psychological well-being and support among faculty members.